2023
DOI: 10.1097/ms9.0000000000000558
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of routine medical checkups for common noncommunicable diseases and associated factors among healthcare professionals in Addis Ababa, Ethiopia, in 2022 a cross-sectional study

Abstract: Background: Routine medical checkups are one strategy for detecting and treating noncommunicable diseases early. Despite the effort to prevent and control noncommunicable diseases in Ethiopia, the prevalence of the problem is significantly increasing. The aim of this study was to assess the uptake of routine medical checkups for common noncommunicable diseases and associated factors among healthcare professionals in Addis Ababa, Ethiopia, in 2022. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…Our study identified several health-related factors associated with the uptake of Periodic Health Examination (PHE). These factors include the presence of chronic diseases supported by other studies (6,14,18,22,26), being insured supported by studies (17,21,25,27,28), and engagement in physical activity (1), a correlation consistent with numerous studies. Understanding these health-related determinants provides valuable insights for healthcare providers and policymakers seeking to enhance preventive healthcare practices.…”
Section: Discussionsupporting
confidence: 78%
“…Our study identified several health-related factors associated with the uptake of Periodic Health Examination (PHE). These factors include the presence of chronic diseases supported by other studies (6,14,18,22,26), being insured supported by studies (17,21,25,27,28), and engagement in physical activity (1), a correlation consistent with numerous studies. Understanding these health-related determinants provides valuable insights for healthcare providers and policymakers seeking to enhance preventive healthcare practices.…”
Section: Discussionsupporting
confidence: 78%